2005
DOI: 10.1097/01.brs.0000172160.78207.49
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stress Distribution in Lumbar Interbody Fusion

Abstract: Interbody fusion cages with larger area of contact between cage and vertebral endplate produces a lower stress distribution pattern. A successful bony fusion restores near physiologic stress distribution pattern. Restoration of near normal load distribution pattern may become an important aim of surgery for discogenic low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…So, for example, when the spine is flexed, the anterior endplate and vertebrae are loaded excessively, and hence the pain on bending, which is a common feature in patients with back pain. Using the finite element analysis, it has also been shown that loads below a cage, which is load bearing, maybe 500% higher than loads below a normal disc [16,30]. The conclusion by McAfee [22] that pain relief following cage fusions seems to be little different from other methods of fusion, despite much better rates of fusion, may be a reflection of loading problems below some cages that remain weight bearing.…”
Section: Discussionmentioning
confidence: 99%
“…So, for example, when the spine is flexed, the anterior endplate and vertebrae are loaded excessively, and hence the pain on bending, which is a common feature in patients with back pain. Using the finite element analysis, it has also been shown that loads below a cage, which is load bearing, maybe 500% higher than loads below a normal disc [16,30]. The conclusion by McAfee [22] that pain relief following cage fusions seems to be little different from other methods of fusion, despite much better rates of fusion, may be a reflection of loading problems below some cages that remain weight bearing.…”
Section: Discussionmentioning
confidence: 99%
“…However there are few studies on interbody fusion which consider the adjacent vertebral body stresses and factors influencing them. Observation of focal loading in the adjacent vertebra, depending on the area of contact between the cage and vertebral endplate is reported [21]. There are studies which identified the bone density and contact area as important factors in estimating the risk of device subsidence and discusses the importance of load sharing mechanism among endplate, cortical shell and cancellous bone while designing new devices [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…The details of dimensions and material properties are given in Table 1. The material properties were taken from literature [20,21]. In the second set of analyses the effect of an uneven endplate, causing voids at the interface, was considered.…”
Section: Methodsmentioning
confidence: 99%
“…First, the ''foot print size'' was clearly critical, if the entire load was transmitted through a small area, then clearly the load per square millimetre of underlying bone would be very high (Polikeit [44] and Kumar [20]). …”
Section: Cagesmentioning
confidence: 99%